2021
DOI: 10.1021/acsomega.1c04950
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Co-Doped Fe2O3 Spindles for the Enhanced Photo-Fenton Catalytic Degradation of Tetracycline

Abstract: Co-doped Fe 2 O 3 spindles with different Co contents were successfully fabricated by a facile one-step hydrothermal method. The crystalline structure, morphology, optical properties, and chemical state of the as-prepared catalysts before and after photo-Fenton reaction were characterized. Co 2+ incorporated into the Fe 2 O 3 lattice was confirmed by the above characterizations. Also, the photocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…As presented in Figure S9, the Raman shifts observed at 213 and 270 cm −1 could be attributed to the A 1g and E g mode characteristic of Fe 2 O 3 . 16,29 When compared with the A 1g Raman mode of Fe 2 O 3 (212.7 cm −1 ) and Sn s :Fe 2 O 3 (212.3 cm −1 ), the red shift and a slightly broader full width at half-maximum (fwhm) on the Raman spectra of Sn q :Fe 2 O 3 (209.6 cm −1 ) indicated the creation of oxygen vacancies, resulting from the Sn doping and quenching step (Table S3). 30 Moreover, compared with the A 1g Raman spectra of Pt q /Fe 2 O 3 (212.7 cm −1 ) and Pt q /Sn s :Fe 2 O 3 (212.3 cm −1 ), that of Pt q / Sn q :Fe 2 O 3 downshifted to 210.2 cm −1 and showed broadened peaks, indicating that more vacancies were generated on Pt q / Sn q :Fe 2 O 3 (Figure S9 and Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Figure S9, the Raman shifts observed at 213 and 270 cm −1 could be attributed to the A 1g and E g mode characteristic of Fe 2 O 3 . 16,29 When compared with the A 1g Raman mode of Fe 2 O 3 (212.7 cm −1 ) and Sn s :Fe 2 O 3 (212.3 cm −1 ), the red shift and a slightly broader full width at half-maximum (fwhm) on the Raman spectra of Sn q :Fe 2 O 3 (209.6 cm −1 ) indicated the creation of oxygen vacancies, resulting from the Sn doping and quenching step (Table S3). 30 Moreover, compared with the A 1g Raman spectra of Pt q /Fe 2 O 3 (212.7 cm −1 ) and Pt q /Sn s :Fe 2 O 3 (212.3 cm −1 ), that of Pt q / Sn q :Fe 2 O 3 downshifted to 210.2 cm −1 and showed broadened peaks, indicating that more vacancies were generated on Pt q / Sn q :Fe 2 O 3 (Figure S9 and Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Crystal lattice distances of 0.25 nm and 0.23 nm were assigned to the Fe 2 O 3 (110) and Au (111) planes, respectively. 34,35 The energy-dispersive X-ray spectroscopy (EDS) mapping in Fig. 1e confirmed that the Au nanoparticles were evenly distributed on the inner surface of the SiO 2 shell, while the Fe 2 O 3 nanowires acted as the inner cable, further suggesting that the Au NPs and Fe 2 O 3 nanowires were not in direct contact.…”
Section: The Physicochemical Characteristics Of Fementioning
confidence: 89%
“…25 The photo-Fenton degradation efficiency of TC by Co-doped Fe 2 O 3 is significantly higher than that of single Fe 2 O 3 . 26 Moreover, Co–Fe co-doped SiO 2 also shows superior catalytic performance, which can achieve 98% degradation of CIP in 10 min. 27 This is because the introduction of other metal ions into the catalyst can accelerate the regeneration of Fe 2+ in the Fenton catalysis process, which has a positive effect on the generation of free radicals and will greatly improve the catalytic efficiency of the catalyst.…”
Section: Introductionmentioning
confidence: 99%